GROWTH ANALYSIS OF Spirulina sp. WITH DIFFERENT COMBINATION OF FERTILIZER - cahya, nilam; Waspodo, Saptono; Setyono, Bagus Dwi Hari (Jurnal Perikanan Unram, 2020)
This study aims to providing a combination of fertilizer (urea, NPK dan TSP) with different doses on the growth of Spirulina sp. This research was conducted in October 2019 which took place in a private graham cendana Blok J no 4, Sekarbela, Mataram City. This study uses a completely randomized design with four treatment namely treatment A: (0 g/l Urea; 0 g/l NPK; 0 g/l TSP) (kontrol), B: (0,2 g/l Urea; 0, 01g/l NPK; 0,004 g/l TSP), C: (0,3 g/l Urea; 0,02 g/l NPK; 0,006 g/l TSP), D: (0,4 g/l Urea; 0,04 g/l NPK; 0,008 g/l TSP).The results of the study for 9 days of culture process in treatment D with a combination of fertilizer (urea, NPK dan TSP) as much (0,4 g/l Urea; 0,04 g/l NPK; 0,008 g/l TSP) the highes density results obtained as much as 831 ind/ml while the lowest value obtained in treatment A (without fertilizer) is as much 505 ind/ml and the highest daily growth rate is obtained in treatment D with a combination of fertilizer (urea, NPK dan TSP) (0,4 g/l Urea; 0,04 g/l NPK; 0,008 g/l TSP) this is as much as 0.413 ind/ml/day while the lowest value obtained in treatment A (without fertilizer) is 0.484 ind/ml/day.